Ecology, Conservation, and Restoration of Tidal Marshes : The San Francisco Estuary - Palaima, Arnas (Book collections on Project MUSE., 2012)
The San Francisco Bay, the biggest estuary on the west coast of North America, was once surrounded by an almost unbroken chain of tidal wetlands, a fecund sieve of ecosystems connecting the land and the Bay. Today, most of these wetlands have disappeared under the demands of coastal development, and those that remain cling precariously to a drastically altered coastline. This volume is a collaborative effort of nearly 40 scholars in which the wealth of scientific knowledge available on tidal wetlands of the San Francisco Estuary is summarized and integrated. This book addresses issues of taxonomy, geomorphology, toxicology, the impact of climate change, ecosystem services, public policy, and conservation, and it is an essential resource for ecologists, environmental scientists, coastal policymakers, and researchers interested in estuaries and conserving and restoring coastal wetlands around the world.